Precarious Living in Jerusalem: Return, Fear, and Sumud. Issue 1 (2nd January 2023) - Isa, R.
Abstract: This essay addresses the Israeli designation of "permanent residency, " more commonly known as Jerusalem residency to which Palestinians in occupied East Jerusalem are confined. Since 1967, the Israeli Ministry of Interior has revoked or refused to renew the residencies of nearly 15, 000 Palestinians. Masquerading as a democracy, Israel hides behind the center of life doctrine—a set of policies and laws that require people to prove their lives center around Jerusalem, or areas occupied in 1948. Property deeds, rental contracts, employment papers, and utility bills are the documents Palestinians must produce to show evidence of belonging to Jerusalem. This bureaucratic wall of Israeli settler colonialism dispossesses Palestinians and employs fear to ethnically cleanse people who trace generations of ancestry to the city. The author shares her struggles in affirming her claims to Jerusalem and practicing sumud .